Monetary Transmission Through the Profit-Sharing Financing Channel in Indonesia - Zaini Ibrahim; Anita; Ratu Fhathunnida (Journal of Islamic Economics and Finance Studies, 2026)
Abstract Profit-sharing financing (PSF) is a leading product of Islamic banking that serves as a stabilizer for the real and monetary sectors, with an average growth rate of 22.05% during the 2009-2024 period. When viewed as an Islamic monetary instrument, this PSF's performance still needs to be tested for its contribution to Indonesia's inflation-targeting framework (ITF). This research aimed to identify the monetary transmission channel through the PSF instrument to encourage economic growth and to stabilize inflation in Indonesia. This study employed a quantitative Structural Vector Autoregression (SVAR) approach to analyze time-series data from 2009:1 to 2024:6. The results indicate that the PSF instrument cannot yet be relied upon to promote economic growth in Indonesia reliably. Likewise, inflation did not respond significantly to shocks to the PSF instrument. Instead, inflation responds more to changes in interest rates in the Interbank Money Market (PUAB). Thus, this article has revealed new findings: monetary transmission through the PSF channel affects only the growth of the Islamic financial sector and has not had a significant impact on the real sector. The implications of these findings encourage monetary authorities to accelerate PSF through regulatory improvements, especially by setting upper and lower limits on PSF yields, establishing minimum share capital for the musharakah scheme, and limiting portions or margins of the murabahah scheme.   Abstrak Profit-sharing financing (PSF) merupakan produk unggulan perbankan Islam yang berperan sebagai stabilisator sektor riil dan moneter, dimana selama periode 2009-2024 rata-rata pertumbuhannya mencapai 22.05%. Jika dilihat fungsinya sebagai salah satu instrumen moneter Islam, performa PSF ini masih perlu diuji kontribusinya dalam dimensi inflation targeting framework (ITF) yang berlaku di Indonesia. Penelitian ini bertujuan untuk mengidentifikasi jalur transmisi moneter yang dilalui instrumen PSF dalam rangka mendorong pertumbuhan ekonomi dan pengendalian inflasi di Indonesia. Studi ini menggunakan pendekatan kuantitatif Structural Vector Autoregression (SVAR) melalui pengujian data time series periode 2009:1 – 2024:6. Hasilnya menunjukkan bahwa instrumen PSF belum bisa diandalkan dalam mendorong pertumbuhan ekonomi Indonesia. Demikian juga shock instrumen PSF tidak direspon signifikan oleh inflasi. Inflasi lebih merespon perubahan suku bunga di pasar uang antar bank. Dengan demikian, artikel ini berhasil mengungkap temuan baru bahwa transmisi moneter melalui jalur PSF hanya berdampak pada pertumbuhan sektor keuangan Islam dan belum berdampak signifikan pada sektor riil. Implikasi dari temuan ini mendorong otoritas moneter untuk melakukan akselerasi PSF melalui perbaikan regulasi terutama penetapan batas atas dan batas bawah terhadap imbal hasil PSF; minimum share capital untuk pembiayaan musyarakah; pembatasan porsi pembiayaan murabahah; atau pembatasan marjin murabahah.